Hepatoprotective effect of royal jelly, grape seed extract, and Lycium barbarum against diethylnitrosamine-induced liver toxicity in rats (Annals of Medical Research, 2021)
None
Keywords: Den (Diethylnitrosamine); Hepatotoxicity; Royal Jelly (Rj); Grape Seed Extract (Gse); Lycium Barbarum Extract (Lbae).